The onset of adaptive immunity in the mouse model of tuberculosis and the factors that compromise its expression. Issue 1 (March 2015) - Robinson, Richard T.; Orme, Ian M.; Cooper, Andrea M.
Summary: Mycobacterium tuberculosis (Mtb) has been evolving with its human host for over 50 000 years and is an exquisite manipulator of the human immune response. It induces both a strong inflammatory and a strong acquired immune response, and Mtb then actively regulates these responses to create an infectious lesion in the lung while maintaining a relatively ambulatory host. The CD4 + T cell plays a critical yet contradictory role in this process by both controlling disseminated disease while promoting the development of the lesion in the lung that mediates transmission. In light of this manipulative relationship between Mtb and the human immune response, it is not surprising that our ability to vaccinate against tuberculosis (TB) has not been totally successful. To overcome the current impasse in vaccine development, we need to define the phenotype of CD4 + T cells that mediate protection and to determine those bacterial and host factors that regulate the effective function of these cells. In this review, we describe the initiation and expression of T cells during TB as well as the fulminant inflammatory response that can compromise T‐cell function and survival.